Invasive Pneumococcal Disease in Neonates Prior to Pneumococcal Conjugate Vaccine Use in South Africa: 2003–2008. Issue 4 (April 2019) - Moodley, Krishnee; Coovadia, Yacoob Mahomed; Cohen, Cheryl; Meiring, Susan; Lengana, Sarona; De Gouveia, Linda; von Mollendorf, Claire; Crowther-Gibson, Penny; Quan, Vanessa; Eley, Brian; Reubenson, Gary; Nana, Trusha; et al.
Abstract : Background: Neonatal invasive pneumococcal disease (IPD) in developing countries is poorly described. We provide a baseline description of neonatal IPD in South Africa, before implementation of the 7-valent pneumococcal conjugate vaccine (PCV7) in 2009. Methods: Data from children (age ⩽ 2 years) with IPD (pneumococcus identified from a normally sterile specimen) from January 2003 to December 2008 were extracted from a national laboratory-based surveillance database. Clinical and laboratory characteristics of IPD among neonates (0–27 days old) was compared with IPD among young children (≥ 28 days ⩽ 2 years). Early-onset IPD (0–6 days old) was compared with late-onset IPD (≥ 7–27 days old). Isolates were serotyped using the Quellung reaction. Results: Overall 27, 630 IPD cases were reported. Of the 26, 277 (95%) with known ages, 6583 (25%) were ⩽ 2 years of age, of which 4.5% (294/6583) were neonates. The estimated annual incidence of neonatal IPD in 2008 was 5 per 100, 000 live births. Fifty-one percent of neonates with IPD presented with early-onset IPD. Case fatality ratios (CFRs) were high in both groups, 31% (28/89) in neonatal IPD versus 26% (614/2383) in non-neonatal IPD ( P = 0.18). Among neonates, the meningitis cases (15/37, 41%) were associated with the highest CFR. The 13-valent pneumococcal conjugate vaccine (PCV13) serotypes accounted for 69% (134/194) of neonatal IPD isolates. Conclusions: Pneumococcal neonatal disease in South Africa was not uncommon before PCV introduction and is associated with a high CFR. The indirect effect on neonatal IPD of PCV rollout requires further evaluation.